2014
DOI: 10.1016/j.jinorgbio.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin and related heterometallic gold(I)–thiolates as potent inhibitors of methicillin-resistant Staphylococcus aureus bacterial strains

Abstract: A series of new heterometallic gold(I) thiolates containing ferrocenyl-phoshines were synthesized. Their antimicrobial properties were studied and compared to that of FDA-approved drug, auranofin (Ridaura), prescribed for the treatment of rheumatoid arthritis. MIC in the order of one digit micromolar were found for most of the compounds against Gram-positive bacteria S. aureus and CA MRSA strains US300 and US400. Remarkably, auranofin inhibited S. aureus, US300 and US400 in the order of 150–300 nM. This is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
41
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 37 publications
10
41
0
3
Order By: Relevance
“…Another drug, auranofin, has recently been reported to have strong antimicrobial activity against several Gram-positive organisms (15)(16)(17), and our results agree well with these reports, as the IC 50 of auranofin was well below the lowest concentration tested (0.6 M).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Another drug, auranofin, has recently been reported to have strong antimicrobial activity against several Gram-positive organisms (15)(16)(17), and our results agree well with these reports, as the IC 50 of auranofin was well below the lowest concentration tested (0.6 M).…”
Section: Resultssupporting
confidence: 93%
“…Auranofin is a gold thiolate compound that has been used to treat rheumatoid arthritis for decades, and it has recently received significant attention due to its antimicrobial potential. A typical dosage for arthritis treatment is 6 mg per day, and the peak plasma concentration after 2 h is 0.025 g/ml; the steadystate blood concentration of gold is 3.5 M. In two separate studies, Hokai et al (15) and Cassetta et al (16) discovered that auranofin significantly inhibits the growth of S. aureus USA300, and they found MICs of 0.2 g/ml and 0.25 g/ml, respectively (ϳ0.3 M). Recently, Siles et al (6) showed that auranofin can inhibit the growth and the formation of Candida albicans biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…Auranofin showed potent growth inhibition against each of the Gram-positive strains tested ( Table 1). The activities against S. aureus are consistent with recent findings of auranofin's antimicrobial activity against drug-sensitive and methicillin-resistant strains of S. aureus (24,25). In addition, we found that auranofin inhibits growth of Enterococcus faecium and Enterococcus faecalis, with an MIC of 0.5 mg/L for both.…”
Section: Resultssupporting
confidence: 91%
“…Data were recorded with a Bruker Smart 1000 CCD (6) or Oxford Diffraction Xcalibur (9) diffractometer. The crystals were mounted in inert oil on glass fibres and transferred to the cold gas stream of the diffractometer.…”
Section: Crystal Structure Determinationsmentioning
confidence: 99%
“…For gold(I), research has been principally focused on compounds with a SAuP or NAuP core, exploiting the analogy to Auranofin [2]. Studies have shown good bactericidal or bacteriostatic results [3][4][5], some of them including Auranofin and related complexes have shown as potent inhibitors of methicillin-resistant Staphylococcus aureus [6], and they also present antitumor, antimalarial, or antirheumatic activities [7]. Other important type of metal complexes presenting good antibacterial activity are those related to N-heterocyclic A C C E P T E D M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%